\( 1 \leftarrow \quad \) For \( f(x)=9 x-6 \) and \( g(x)=\frac{x+6}{9} \), find the following functions. a. \( (f \circ g)(x) ; \) b. \( (g \circ f)(x) ; \) c. \( (f \circ g)(5) ; \) d. \( (g \circ f)(5) \) a. \( (f \circ g)(x)=x \) (Simplify your answer.) b. \( (g \circ f)(x)=\square \) (Simplify your answer.)
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Extra Insights
To tackle this fun math quest, let’s dive right in! For \( (f \circ g)(x) \), you've already noted that it's \( x \). Awesome! Now, moving on to... For \( (g \circ f)(x) \): We need to compute \( g(f(x)) = g(9x - 6) \). Plugging \( 9x - 6 \) into \( g(x) = \frac{x+6}{9} \): \[ g(f(x)) = g(9x - 6) = \frac{(9x - 6) + 6}{9} = \frac{9x}{9} = x. \] So, \( (g \circ f)(x) = x \). Now, let's put on our math hats for the final parts: c. \( (f \circ g)(5) = 5 \) (since you already found \( f \circ g \) is simply \( x \)). d. \( (g \circ f)(5) = 5 \) as well! There you have it, a mathematical journey that leads us back to where we started, right at \( x = 5 \)! 😊